2014
DOI: 10.1186/1754-6834-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structures differentiated in a single-chamber air-cathode microbial fuel cell fueled with rice straw hydrolysate

Abstract: BackgroundThe microbial fuel cell represents a novel technology to simultaneously generate electric power and treat wastewater. Both pure organic matter and real wastewater can be used as fuel to generate electric power and the substrate type can influence the microbial community structure. In the present study, rice straw, an important feedstock source in the world, was used as fuel after pretreatment with diluted acid method for a microbial fuel cell to obtain electric power. Moreover, the microbial communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The second way of obtaining a biocathode is to polarize the electrode at a potential lower than the open circuit potential. The cathode polarization can result from MFC operation (potential may vary) [7][8][9][10] or from potentiostatic control (potential is constant) [11][12][13][14][15][16][17][18]. This method is widely used to form effective OR-biocathodes in many environments, among them sewage sludges or/and wastewater [8,13,15,18], industrial/agricultural wastes [7,9], seawater and sediments [14,17], soil and/ or derived leachate [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The second way of obtaining a biocathode is to polarize the electrode at a potential lower than the open circuit potential. The cathode polarization can result from MFC operation (potential may vary) [7][8][9][10] or from potentiostatic control (potential is constant) [11][12][13][14][15][16][17][18]. This method is widely used to form effective OR-biocathodes in many environments, among them sewage sludges or/and wastewater [8,13,15,18], industrial/agricultural wastes [7,9], seawater and sediments [14,17], soil and/ or derived leachate [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that chicken feathers can be successfully employed as a cheap substrate for electricity production in MFC. In a different study, rice straw hydrolysate was used for electricity production by Wang et al (2014). In presence of 400 mg-COD/L, a power density of 137.6 ± 15.5 mW/m 2 was obtained.…”
Section: Agro Wastesmentioning
confidence: 99%
“…[1][2][3][4] Fueling MFC with renewable resources is now considered as one of the promising strategies to develop sustainable energy systems on earth. [5][6][7][8] Biomass is the most abundant renewable bioresource for sustainable bioenergy production. 9 For example, about 7 Â 10 8 tonnes of agricultural biomass could be produced annually in China.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, MFCs fueled with wheat/rice straw hydrolysate were established with the mixed microbial community. 5,12 By using hydrothermal treated wheat straw hydralysate as the substrate, $148 mW m À2 power output was obtained by using a two chamber MFC inoculated with mixed microbial community. 12 Another biomass hydrolysate with about 1 time higher power output (293 mW m À2 ) was also developed by using acidic treated rice straw hydrolysate and anaerobic sludge as the substrate and inoculum, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation